2020
DOI: 10.1530/eje-20-0066
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being and personality in relation to weight loss following behavioral modification intervention in obese women with polycystic ovary syndrome: a randomized controlled trial

Abstract: Objective Little is known about how lifestyle affects psychological well-being in overweight women with polycystic ovary syndrome (PCOS). We investigated the effects of behavioral modification on psychological well-being and the impact of well-being and personality traits on successful weight loss. Design A 4-month randomized controlled trial with a 12-month follow-up at a University Hospital. Methods Sixty-eight women with PCOS, aged 18 to 40 years with a BMI ≥27 kg/m2, were randomized (1:1) into a behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…There was evidence of improved anxiety, lower depressed mood and overall higher general health in the intervention group with no change in the minimal intervention group. 86 Exercise alone as intervention in PCOS has been studied. 87 Most studies of exercise intervention are small and involved varying exercise interventions-aerobic, resistance and combined exercise.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…There was evidence of improved anxiety, lower depressed mood and overall higher general health in the intervention group with no change in the minimal intervention group. 86 Exercise alone as intervention in PCOS has been studied. 87 Most studies of exercise intervention are small and involved varying exercise interventions-aerobic, resistance and combined exercise.…”
Section: Lifestyle Interventionsmentioning
confidence: 99%
“…In the present study, the unplanned outpatient admission rate of patients with PCOS in the experimental group (8.57%) was lower than that in the control group (35.48%). The reason for this phenomenon may be that with the healthy behavior and negative emotions regarding improving metabolic disorder relief, participants experienced a reserve in the physiological and mental system (Jiskoot et al, 2020;Oberg et al, 2020), which may explain the healthier lifestyle and the lower unplanned admission rates in our study. A previous study reported that unplanned admission would also increase the psychological burden and economic pressure (Bosco et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…More recently, a cross-sectional study in 501 women with PCOS [ 131 ] and two RCTs [ 44 , 132 ] explored the use of self-management strategies [ 131 ] and behavioural modification interventions [ 44 , 132 ] in PCOS. In the cross-sectional study, implementation of physical activity self-management strategies improved the likelihood of meeting physical activity recommendations, but had no association with BMI.…”
Section: Traditional Lifestyle and Weight Managementmentioning
confidence: 99%
“…In the RCTs, only the behavioural modification programme and not the control (general healthy lifestyle recommendations) produced significant weight loss after four months. A significantly greater proportion of women in the intervention group also improved menstrual regularity [ 44 ] and psychological well-being (lower anxiety and depressive symptoms) [ 132 ] when compared to the control group. The women who achieved greater weight loss reported higher social desirability and lower embitterment scores on a personality trait assessment measure [ 132 ].…”
Section: Traditional Lifestyle and Weight Managementmentioning
confidence: 99%